The existence and characterization of Mycorrhiza Rhizoctonia sp. Binucleate in traditional medicinal orchid (Plocoglottis lowii Rchb.f.) from Sanggau Malay Ethnic West Kalimantan - Rista Delyani; Sigit Normagiat; Rita Kurnia Apindiati (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2019)
The conversion of forest for another purpose has made the population and diversity of medicinal plants increasingly threatened. The ex situ conversion by cultivation is needed to provide the suitable environment to ensure the plants grow in their natural habitat and maintain their properties. One of the traditional medicinal plants in Sanggau Malay which has been believed to neutralize the toxin is “anggrek penawar racun” (Plocoglottis lowii Rcbb.f.). This research was important to be done since there was no data and information about mychorrizal type associated to root of orchid P. lowii Rchb.f. in its natural habitat. The aim of this research was to find out the data and information about the types, the characteristics, and the percentage of mycchorizal fungal infection in root tissue for conservation and cultivation purpose. The research used 10% KOH heating method and freehand section coloring using Trypan Blue, Acid Fushin dan Safranin-O conducted in cross section of the roots. The results showed that there was only one species of fungi and it was identified as Rhizoctonia sp. Binucleate type. The highest percentage of mycchorizal infection occurred at the tip of the roots (90%). It has been found that the location of mychorrizal infection has occurred between the epidermis and cortex. It is needed to do the further study about mychorrizal isolate Rhizoctonia sp. effectiveness in the growth of P. lowii Rchb.f in the cultivated land.